Jurnal Rancang Bangun Sistem Informasi Reseller Dengan Pendekatan Customer Relationship Management Berbasis Web - Ruri Mutiara Ayuni; Nugraha, Nugraha; Anggun Fergina (Universitas Muhammadiyah Riau, 2025)
This study aims to design and implement a web-based reseller information system at Mutiara Cell with a Customer Relationship Management (CRM) approach to answer the needs of digital transformation in improving operational efficiency and managing business relationships. Mutiara Cell is a company that distributes electric credit and digital products that involves many reseller partners, but still faces obstacles in recording transactions, managing data, and reporting finances that are done manually. The system developed is designed to facilitate administrators and resellers in ordering products, uploading proof of payment, managing bills, and reporting sales digitally and in an integrated manner. The development uses a waterfall model with stages of needs analysis, design, implementation, and testing, and uses PHP Native as a programming language and Black Box Testing to ensure system functionality. The results show an increase in operational efficiency, data access speed, and accuracy in transaction management. In addition, the user-friendly interface supports convenience in accessing services, and the CRM approach has been proven to strengthen business relations and increase partner loyalty. This system is considered feasible to use and is a long-term digital solution in supporting operational activities and managing relationships with resellers more professionally.